Transcatheter Aortic Valve Replacement in Patients ≥80 and <80 Years of Age with Aortic Valve Stenosis at Moderate Surgical Risk: Findings from an Observational Study in the Vietnamese Population - Khoa Quoc Nguyen; Duong Van Nguyen; Thuy Thi La; Tan Van Nguyen; The Ngoc Ha Than; Thach N. Nguyen; Hoang VK Dinh; Cong Duc Nguyen; Nhan Vo Thanh (Cardiovascular Innovations and Applications)
Objectives: The increasing number of elderly patients with severe aortic valve stenosis undergoing transcatheter aortic valve replacement (TAVR) has prompted concerns regarding their clinical outcomes compared with the younger population. This study evaluated the outcomes of TAVR on the basis of age group (<80 or ≥80 years) among Vietnamese patients with severe aortic valve stenosis at intermediate surgical risk. Methods: From March 2017 to December 2022, 21 patients ≥80 years of age and 69 patients <80 years of age underwent TAVI at a single center. Clinical characteristics, procedures, and outcomes at 30 days and 1 year were compared with the Valve Academic Research Consortium (VARC-2) criteria. Results: Patients ≥80 years of age had a higher prevalence of comorbidities but no significant differences in other clinical characteristics and procedures. No statistically significant differences were observed in procedural mortality (4.8% vs. 0.0%, P = 0.233), 30-day mortality (5.0% vs. 1.5%, P = 0.405), and 1-year mortality (11.8% vs. 3.7%, P = 0.241) between age groups. Major endpoints at specified time points also showed no significant differences. Conclusions: TAVR in patients with aortic stenosis at intermediate surgical risk has similar clinical outcomes at 30 days and 1 year, according to VARC-2 criteria, with no statistically significant age-associated differences (≥80 vs. <80 years). However, further studies with larger patient populations are needed to better understand the effects of age on TAVI outcomes in patients with similar characteristics.